Triagem de fungos da amazônia como potenciais fornecedores de lipases para aplicação em biocatálise - Romano, Israel Paes (2009)
In recent years, there has been a growing worldwide concern about the impact of human actions on the environment. The implementation of the concept of sustainable development in the various productive activities has become a imperative today. For industry, this theme can define survival or not from certain sectors related to chemistry (SANSEVERINO, 2000). Fortunately, biotechnology also offers a growing potential to meet demand process and products in greater harmony with the concept of sustainability (OECD, 2001; BUCHHOLZ et al., 2005). In this sense, one of the most promising tools in biotechnology is the field of applied biocatalysis, also called by some authors biotransformation or enzymatic technology (BUCHHOLZ et al., 2005; BOMMARIUS and RIEBEL, 2004). The advantages of using enzymes as biocatalysts in processes industrial processes have become increasingly evident: great versatility of catalyzed reactions, mild reaction conditions, regal nature, chemo and enantioselective are the most frequently cited in the literature. (CARVALHO et al., 2005; SILVA et al., 2005) Such characteristics allow enzymes promote reactions that could hardly be carried out by the techniques of conventional organic synthesis (SILVA et al., 2005). They also offer a higher yield alternative compared to traditional catalysis processes chemistry (CASTRO et al., 2004). From an ecological point of view, the most important is that the high selectivity and efficiency of biological catalysts provide reactions with few by-products and less energy consumption, making the enzymes an environmentally cleaner alternative to traditional chemical catalysis (SCHMID et al., 2001). Many industry sectors are strong candidates for doing and several are already doing - large-scale use of these advantageous aspects of biocatalysis.